An Analysis of the Constitutional Court Ruling On the Annulment of the Provisions on Coastal Water Concessions (HP-3) - Damanik, M. Riza (Indonesia Law Review, 2013)
After the annulment of the Coastal Water Concessions (HP-3) in 16 June 2011, traditional fisher folk organization leaders found a great fighting spirit to further follow-up the Constitutional Court Ruling to support their daily lives. For those who are being “evicted” from their living space (the coastal waters), they want to reclaim their rights through constitutional ways. Likewise, those who (feel to) have lost their existence as Indonesian traditional fisher folk are impatient to find out whether there is a breakthrough in the Constitutional Court Ruling that can restore the fisher folk’s family way of life. The ruling itself was complex and not easy to understand: 169 pages, with complex writing systematic and typical legal language. For this reason, the analysis of the Constitutional Court Ruling regarding the Judicial Review on Law No. 27 of 2007 on the Management of Coastal Areas and Small Islands was necessary in order to provide a simpler representation of the Constitutional Court Ruling, and one that is expected to trigger a constructive discussion to implement the favorable parts of the decree for the greatest welfare of the people.